Efektivitas Strategi Practice Rehearsal Pairs terhadap Hasil Belajar Siswa pada Mata Pelajaran Fikih Kelas VII MTsN Padang Panjang - Rusmani Rusmani; Syarifatul Hayati; Diana Sartika (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
The practice rehearsal pairs strategy is a practice strategy in pairs with friends and groups. With practice rehearsal pairs learning strategies can make students more active in the learning process and can improve learning outcomes. Based on the results of interviews conducted by researchers at MTsN Padang Panjang. There are still many student scores below KKM (80). For this reason, researchers are interested in implementing practice rehearsal pairs strategies in improving the learning outcomes student of grade VII A MTsN Padang Panjang. This type of research is an experiment with randomize control group only design, samples are selected using purposive sumpling techniques. This research use by two sample, the are experimental class and control class. This research was conducted in the odd semester of the 2023/2024 academic year, namely class VII A as an experimental class and class VII D as a control class. The instrument used tests using the t-test hypothesis. data processing using SPSS. The implementation of the practice rehearsal pairs strategy in class VII A MTsN Padang Panjang jurisprudence subjects has gone well. This is evident from the results of supervision of the implementation of learning whose value is 90 with very good creteria. Student learning outcomes also improved after the implementation of the practice rehearsal pairs strategy. This is evident from the average score of the experimental class of 93 which is higher than the control class which gets an average score of 88. Based on the results of the hypothesis test, a tcount result of 9,360> ttable 1,670 was obtained. So it can be concluded that the application of practice rehearsal pairs learning strategies is effective in improving student learning outcomes on fikih subject in class VII A MTsN Padang Panjang.